Researches on the Nepalese mycoflora - 2, Checklist of Macrofungi (Mushrooms) Book Review - Tiwari, R. D. (Ecoprint: An International Journal of Ecology, 2014)
Not available (Book review) DOI: http://dx.doi.org/10.3126/eco.v19i0.9859 Ecoprint An International Journal of Ecology Vol. 19, 2012 Page: 91-91 Uploaded date: 2/14/2014